International digital currencies and their impact on monetary policy: An exploration of implications and vulnerability - Thorsten Proettel (Universität Hohenheim, Fakultät Wirtschafts- und Sozialwissenschaften, 2019)
The objective of this discussion paper is to explore the consequences for monetary policy from the establishment of an international digital currency modeled like Libra. For this purpose, a basic assessment of the behavior of economic agents is conducted and possible conflicts with monetary policy are analyzed. Furthermore, a simple approach is developed to estimate the nature and extent of vulnerability for 42 currencies. The results suggest that currencies from developing countries and from developed nations are vulnerable in different ways. In the end, a stronger convergence of central bank policies could result. Thus, the introduction of an international digital currency represents a turning point for monetary policy.
urn:nbn:de:bsz:100-opus-16730
Keywords: E42; E52; E58; 330; monetary policy; digital currency; blockchain; effective lower bound